Physicochemical, structural, and adsorption characteristics of DMSPS-co-DVB nanopolymers - Bosacka, Alicja; Zienkiewicz-Strzalka, Malgorzata; Derylo-Marczewska, Anna; Chrzanowska, Agnieszka; Blachnio, Magdalena; Podkoscielna, Beata (Frontiers in Chemistry, 2023)
The aim of this work is the synthesis and characterization of the series of S,S'-thiodi-4,1-phenylene bis(thiomethacrylate)-co-divinylbenzene (DMSPS-co-DVB) nanomaterials. The series of new nanopolymers including three mixed systems with different ratios of DMSPS and DVB components: DMSPS-co-DVB=1:1, DMSPS-co-DVB=1:2, and DMSPS-co-DVB=1:3 was synthesized in the polymerization reaction. The research task is to investigate the influence of the reaction mixture composition on morphological, textural and structural properties of final nanosystems including size, shape, and agglomeration effect. The advanced biphasic nanomaterials enriched with thiol groups were successfully synthesized as potential sorbents for binding organic substances, heavy metals, or biomolecules. To determine the impact of the DMSPS monomer on the final properties of DMSPSco-DVB nanocomposites several techniques were applied to reveal the nano-dimensional structure (SAXS), texture (low-temperature nitrogen sorption), general morphology (SEM), acid-base properties (potentiometric titration), and surface chemistry and phase bonding effectiveness (FTIR/ATR spectroscopy). Finally, kinetic studies of aniline (AN) sorption on polymeric materials were performed.